Calcium isotope signature: new proxy for net change in bone volume for chronic kidney disease and diabetic rats. Issue 12 (8th November 2017) - Tanaka, Yu-ki; Yajima, Nobuyuki; Higuchi, Yusuke; Yamato, Hideyuki; Hirata, Takafumi
Abstract : Herein, we measure the Ca isotope ratios ( 44 Ca/ 42 Ca and 43 Ca/ 42 Ca) in serum and bone samples collected from rats with chronic kidney disease (CKD) or diabetes mellitus (DM). Abstract : Herein, we measure the Ca isotope ratios ( 44 Ca/ 42 Ca and 43 Ca/ 42 Ca) in serum and bone samples collected from rats with chronic kidney disease (CKD) or diabetes mellitus (DM). For the serum samples, the isotope ratios are lower for the CKD ( δ 44 Ca/ 42 Caserum = 0.16 ± 0.11‰; 2SD, n = 6) and the DM ( δ 44 Ca/ 42 Caserum = −0.11 ± 0.25‰; 2SD, n = 7) rats than that for the control rats ( δ 44 Ca/ 42 Caserum = 0.25 ± 0.04‰; 2SD, n = 7). Bone samples from two distinct positions of 20 rats in total, namely, the center and proximal parts of the tibial diaphysis, are subject to Ca isotope analysis. The resulting δ 44 Ca/ 42 Ca values for the bone of the proximal part are about 0.3‰ lower than that for the serum samples from the same rats. The larger isotope fractionations between the serum and bone are consistent with previously reported data for vertebrate animals ( e.g., Skulan and DePaolo, 1999), which suggests the preferential incorporation of lighter Ca isotopes through bone formation. For the bones from the control and CKD rats, there were no differences in the δ 44 Ca/ 42 Ca values between the positions of the bone. In contrast, the δ 44 Ca/ 42 Ca values of the bone for the DM rats were different between the positions of the bone. Due to the lower bone turnover rate for the DM rats, the δ 44 Ca/ 42 Ca for the middle of the diaphysis can reflect the Ca isotopes in the bone formed prior to the progression of DM states. Thus, the resulting δ 44 Ca/ 42 Ca values show a clear correlation with bone mineral density (BMD). This can be due to the release of isotopically lighter Ca from the bone to the serum. In the present study, our data demonstrate that the δ 44 Ca/ 42 Ca value for serum can be used as a new biomarker for evaluating changes in bone turnover rate, followed by changes in bone volume.